PENGENALAN PERAN TEKNIK KIMIA DALAM APLIKASI KEAMANAN PANGAN (FOOD SAFETY) DI DUSUN PELEM WULUNG BANGUNTAPAN KABUPATEN BANTUL - Sri Rahayu Gusmarwani (Universitas Sahid Surakarta, 2016)
Three pilars of an university activities are Education and Teaching, Research, and Community Service. Community was as one of university’s stake holder need some knowledge and technologies that could be applied for their lives. Community service was done in order for applicating and publicating of science and technology. Community service was also done for minimizing gap between university and community. Chemical Engineering, one of Department in Institute Technology and Science AKPRIND Yogyakarta, take a role play in food safety management, cause one of curriculum in Chemical Engineering was Food Technology. Food Safety in chemical engineering mean activities or systems that can be reduce, eliminate or protect food from food hazardous materials.